Effectiveness of Spirulina platensis Extract on Wound Area and TNF-a Levels on Blood: Experimental Studies In Wistar Rats Made Artificially by Vulnus Scissum and Infected by Staphylococcus aureus - Olvaria Misfa; Renni Yuniarti; Yan Wisnu Prajoko (Research Centre of Inorganic Materials and Complexs, 2020)
This research uses randomizedpost-test only control group design. Thirty-two (32) male Wistar rats with incised skin and infected with S. aureusdivided into 4 groups, namely the group given S.platensisextract at a dose of 500 mg / kgBB / day (X1) and a dose of 750 mg / kgBB / day (X2 ), the negative control group was given saline solution (C1), and the positive control group was given amoxicillin 150 mg / kg orally(C2). Wound area measurements were taken on day 14 and serum TNF-? levels were examined on day 14 using the ELISA method. Data analysis was performed with one way ANOVAtestand continued with Post Hoc Test LSD.The results showed mean size of wound closure on the 14th day in groups X1, X2, C1 and C2 is 8095.74; 6270.98;15502.69; 11475.20micrometer with p <0.001. The mean TNF-? serum levels in the 14th day of X1, X2, C1, and C2 groups were 270.75; 222.83; 1730.33; 385.75pg / ml with p <0.001. Post Hoc Test of wound area showed significant differences between groups. Post Hoc Test TNF-? levels showed significant differences between treatment groups X1 and X2 with group C1.Spirulina platensisextract 500mg / kgBB / day and 750 mg /kgBB/ day have the smallest wound area significantly and reduce TNF-? levels on blood.